1992
DOI: 10.1001/archsurg.1992.01420020103014
|View full text |Cite
|
Sign up to set email alerts
|

Double Gloving

Abstract: Health care workers, particularly surgeons, understand the importance of preventing contamination from blood of patients infected with deadly viruses. One of the most common areas of contamination is the hands and fingers due to the failure of glove protection. There are varying opinions regarding the frequency of glove failure, the necessity of wearing two gloves for added protection, and the ability to operate when wearing two gloves. We performed a prospective, randomized, trial of 143 procedures involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The failure rate from blood contamination of the fingers in one study of surgeons was significantly decreased from 13 to 2% (p < 0.005) [37]. Another similar study among surgeons reported blood contamination to be 51% with single gloves and 7% with double gloves [41]. This particular trial also reported that 88% of the surgeons who tested double gloving found the technique acceptable.…”
Section: Glove Propertiesmentioning
confidence: 99%
“…The failure rate from blood contamination of the fingers in one study of surgeons was significantly decreased from 13 to 2% (p < 0.005) [37]. Another similar study among surgeons reported blood contamination to be 51% with single gloves and 7% with double gloves [41]. This particular trial also reported that 88% of the surgeons who tested double gloving found the technique acceptable.…”
Section: Glove Propertiesmentioning
confidence: 99%
“…As colorectal surgery is generally associated with a higher SSI rate than other types of surgeries, the prevention of glove perforation during colorectal surgery may have a greater impact on decreasing the SSI rate than other protection measures [ 5 7 ]. To avoid breaching the protective barrier, thereby protecting both the medical workers and the patients from harm, double gloving or changing gloves at routine intervals during surgery is recommended [ 3 , 8 , 9 ].…”
mentioning
confidence: 99%